2023
DOI: 10.1002/fer3.16
|View full text |Cite
|
Sign up to set email alerts
|

Gender digital divide in education 4.0: A systematic literature review of factors and strategies for inclusion

Iris Cristina Peláez‐Sánchez,
Carlos Enrique George Reyes,
Leonardo David Glasserman‐Morales

Abstract: The gender digital divide (GDD) is a phenomenon that refers to the inequalities and differences between men and women in accessing the digital ecosystem in various environments, such as the scenarios of Education 4.0. Bridging the GDD in access, use, and appropriation of technologies would promote the digital inclusion in spaces traditionally dominated by men. A systematic literature review was conducted using seven databases, considering Scopus and Web of Science. Through this, the factors with the most signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…On the other hand, the literature review on this topic has revealed that the development of 21st-century technologies and the evolution of Education 4.0 have widened the disparities in equitable technology use (Peláez-Sánchez et al 2023). This phenomenon has led to an increase in the digital divide, limiting access, utilization, and appropriation of complex learning environments based on technologies such as augmented reality, virtual reality, data analytics, and blockchain, among others, for vulnerable groups, including women (Miranda et al 2021).…”
Section: The Metaverse: Immersive Environment In Educationmentioning
confidence: 99%
“…On the other hand, the literature review on this topic has revealed that the development of 21st-century technologies and the evolution of Education 4.0 have widened the disparities in equitable technology use (Peláez-Sánchez et al 2023). This phenomenon has led to an increase in the digital divide, limiting access, utilization, and appropriation of complex learning environments based on technologies such as augmented reality, virtual reality, data analytics, and blockchain, among others, for vulnerable groups, including women (Miranda et al 2021).…”
Section: The Metaverse: Immersive Environment In Educationmentioning
confidence: 99%